The Effects of Small-Sided Games on Fitness Components and Technical Abilities among Youth Soccer Players - ALI MD NADZALAN; Mohd Faridz Ahmad; Jeffrey Fook Lee Low (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2024)
Small-sided games (SSG) is one of the increasingly popular training method in developing fitness components and technical abilities among soccer players. The objective of this study was to investigate the effectiveness of SSG training towards player's fitness components and technical abilities after six weeks of training program among youth soccer players. Sixty youth soccer players (M = 19.98 years of age; SD = 0.97) were recruited in this study and were divided into SSG intervention group (IG, N = 30) and control group (CG, N = 30). Agility, speed, cardiovascular endurance, passing and dribbling tests were conducted pre- and post- six weeks of training. Results showed that there was a statistically significant difference on speed, passing, dribbling and VO2max in the post-test among the IG group. When compared to CG, IG were shown to perform better at speed, dribbling and VO2max as it showed a significant difference between groups. As a conclusion, SSG training method can improve speed, passing, dribbling and VO2max. Therefore, this study recommends SSG training to be apply towards youth soccer players.